Blank Verse: History and Evolution - Raziq, Abdul; Ali, Nasir; Taj, Rukhshanda (sourcecoder, 2024)
Blank verse, a form of poetry characterized by its unrhymed lines with a regular meter, has a rich history that spans centuries and cultures. Its evolution can be traced back to the works of ancient Greek and Latin poets, such as Lucretius and Virgil, who employed unrhymed lines in their epic poetry. However, it was during the Renaissance period in England that blank verse truly flourished, notably with the works of William Shakespeare and Christopher Marlowe. These playwrights used blank verse extensively in their plays, elevating it to a prominent position in English literature. Over time, blank verse evolved further, adapting to different languages and poetic traditions, including Urdu poetry. In Urdu poetry, blank verse found its own unique expression, blending with the rich poetic heritage of the language. Urdu poets like Molana Altaf Hussain Hali, Abdul Halim Shararr and Noon Meem Rashid experimented with blank verse, infusing it with the lyrical beauty and emotional depth characteristic of Urdu poetry. The form provided Urdu poets with a flexible structure that allowed for nuanced expression and exploration of diverse themes, ranging from love and longing to social and political commentary. Through its evolution in Urdu poetry, blank verse has contributed significantly to the richness and diversity of the poetic tradition, demonstrating its enduring relevance and adaptability across cultures and languages. In this research article, an attempt has been made to present the history and evolution of blank verse in a useful manner.